A Survey of ELE Students’ Perception about Online Class through WhatsApp - Fika Ahsantu Dhonni; Nunung Suryati; Furaidah Furaidah (Universitas Negeri Malang, 2021)
Abstract: Corona Virus Disease (COVID-19) has affected education system around the world. Schools and universities including Universitas Negeri Malang (UM) are not able to continue face-to-face meetings, thus online classes become an option to carry out. However, as our education system tends to adopt conventional system, moving to the online mode is challenging at all aspects. Therefore, this study is set out to explore the implementation of online learning. More particularly, the study looked at how students of English Language Education study program perceive the online classes they undertake during pandemic using WhatsApp as the primary medium of teaching and learning. By distributing an online survey and analyzing the data using a descriptive quantitative approach, the result of this study showed that the students had positive responses towards online teaching and learning process via WhatsApp. However, the students still needed direct interaction, which involved affection from their teacher, which cannot be obtained through online classes. In conclusion, WhatsApp as a supplementary tool has been proven effective in substituting face-to-face learning activities, as perceived by students participated in this study. Keywords: online learning, perception, WhatsApp Abstrak: Corona Virus Disease (COVID-19) telah mempengaruhi sistem pendidikan di seluruh dunia saat ini. Banyak sekolah dan universitas termasuk Universitas Negeri Malang (UM) tidak dapat melanjutkan pertemuan tatap muka, sehingga perkuliahan secara daring menjadi alternatif yang dipilih. Akan tetapi, oleh karena sistem pendidikan di Indonesia cenderung menggunakan sistem konvensional, perkuliahan daring menghadirkan berbagai tantangan. Oleh karena itu, penelitian ini didesain untuk mencermati implementasi dari perkuliahan daring. Secara spesifik, penelitian ini meneliti persepsi mahasiswa Program Studi Pendidikan Bahasa Inggris tentang pelaksanaan perkuliahan daring yang mereka telah jalani selama pandemi ini melalui media WhatsApp. Dengan menyebarkan angket dan menganalisa data secara kuantitatif deskriptif, hasil penelitian ini menunjukkan bahwa mahasiswa memiliki respon positif terhadap proses belajar mengajar daring melalui WhatsApp. Namun, tidak dapat dipungkiri bahwa mereka tetap membutuhkan interaksi langsung dengan dosen yang tidak dapat diperoleh melalui kelas daring ini. Dari penelitian ini dapat diambil kesimpulan bahwa WhatsApp sebagai media pendukung terbukti efektif dalam menggantikan kegiatan pembelajaran offline sebagaimana dipersepsikan oleh mahasiswa yang berpartisipasi dalam penelitian ini. Kata kunci: pembelajaran online, persepsi, WhatsApp